Application of Chicken Sausage Using Psyllium Husk Flour as a Natural Antioxidant - Maritsha Dinda Putri; Susilo Agus; Evanuarini Herly (BIO Web of Conferences)
The use of psyllium husk flour which is rich in fiber and bioactive compounds, can increase the nutritional value of chicken sausages. This study aims to develop chicken sausages using Psyllium Husk Flour (PHF) as a source of natural antioxidants. PHF is known to have high fiber and bioactive compound content that can function as natural antioxidants. The method used is a laboratory experiment using a Completely Randomized Design (CRD) ANOVA with 4 treatments and 5 replications, if different results are obtained between treatments, further Duncan’s Multiple Range Test (DMRT) will be carried out. The treatment of adding psyllium husk flour to chicken sausages is without addition (T0), 5% (T1), 10% (T2) and 15% (T3). The results of adding PHF showed a decrease in moisture content and cooking loss, as well as an increase in water holding capacity (WHC), yield and antioxidants, while increasing organoleptic quality, including color, texture, taste, and aroma that are preferred by panelists. It can be concluded that the best chicken sausage is produced with the addition of 15% PHF based on the physicochemical properties.